Effect of Pichia pastoris host strain on the properties of recombinant Aspergillus niger endoglucanase, EglB - Shazilah Kamaruddin; Nor Muhammad Mahadi; Rosli Md Illias; Osman Hassan; Suhaila Sulaiman; William Broughton; Izwan Bharudin; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Malaysian Society for Microbiology, 2024)
Malaysian Journal of Microbiology, Vol 14(6) Special Issue 2018, pp. 554-562